A inserção da responsabilidade social do setor bancário no contexto da governança corporativa - Sartore, Marina de Souza (Universidade Federal de São Carlos, 2006)
The banking sector was one of the brazilian economy s sector which most provoked unemployment in the beggining of the 90s. At the same decade, it was possible to see, in the economic and social scenery, the rise of corporate social responsibilitty s practices in which the social actions, aiming the workers are included. The relation between the social and the capital is a discussion that crosses centuries and it is always presented as a contradictory relation. This research aims to understand if the contradition between the social (represented by the corporate social responsibilities practices) and the capital does exist by analysing the bankers discourse. The analysis of the social reports and interviews were necessary to reach this objective. The results obtained demonstrate that, the social logic implanted in the corporate social responsibilities practices inserts itself in the financial social logic of corporative governance, opening ways to a financial sociology s approach in the banking sector.
Keywords: Administração - responsabilidade; Sociologia econômica; Desenvolvimento sustentável; Corporate social responsability; Banking sector; Corporate governance; Workers; Financial sociology; ENGENHARIAS::ENGENHARIA DE PRODUCAO